Estudo das propriedades de concretos com substituição parcial de agregado natural por RCD - Frotte, Camila (2015)
The civil construction sector is one of those responsible for waste generation and the extraction of natural resources. In order to contribute to sustainability, there is the importance of studies on the properties of construction and demolition waste (CDW) in order to encourage recycling, reducing consumption of natural raw materials and waste disposal on the environment. The present work deals with the study of properties of concrete with partial replacement of natural aggregate by CDW. The recycled aggregate in question is a type of crusher run aggregate from a CDW recycling plant, the Usinas de Recicláveis Sólidos do Paraná (USIPAR), located in Almirante Tamandaré - PR. The recycled aggregate was characterized in respect to their particle size and other physical characteristics. The fine fraction of recycled aggregate was chosen to replace the natural aggregate for concrete production. Other characteristics of this fraction were analysed, as pulverulent material content, specific weight and water absorption. Concretes were produced with different substitution rates of natural aggregate by recycled aggregate (0%, 25%, 50%). Then the influence of the replacement content in concrete properties was assessed, in respect to their workability, absorption, void ratio, specific weight, compressive strength, tensile strength by diametrical compression and elasticity modulus. It was found that the aggregate in question is classified as mixed, and that the granulometric distribution of the fine fraction of the recycled aggregate is suitable for use in concrete, as well as its pulverulent content and absorption. It was found that increasing the substitution rate of natural aggregate by recycled aggregate reduced the workability, the dry specific weight and saturated specific weight, and modulus of elasticity of concretes, as well as increased absorption and void ratio of concretes. The real specific weight of the concrete was not influenced by the replacement content. In regard to the compression and tensile strength, the replacement of natural aggregate by recycled aggregate led to a decrease in concrete strength. The concrete with a 50% replacement level obtained a greater compressive strength than the concrete with 25% replacement level, and the same tensile strength as the reference concrete.